Indonesia’s Confidence Crisis: A Bibliometrics Analysis - Cahyani, Cindy Amalia; Yulianingsih, Yulianingsih; Megawanti, Priarti (Universitas Gadjah Mada, 2024)
The low self-confidence of students in Indonesia has an impact on many aspects. In education, students often plagiarize their friends' answers to get good grades. Apart from that, cases of bullying, body shaming, and even suicide are caused by students' low self-confidence. This article aims to bibliometrically examine research trends on self-confidence in Indonesia. This article uses bibliometric analysis to conclude the position of the self-confidence crisis on the research map in Indonesia. With the help of Publish or Perish software from Harzing and VOSviewer, 1,000 articles were obtained. These articles were then analyzed based on scientific impact categories from Google Scholar, assisted by Publish or Perish, as well as visual displays from VOSviewer. The display produced by VOSviewer shows that self-confidence is still something that can be researched, especially if it is associated with several keywords that are far from the word self-confidence. Apart from that, from the search results, it was found that parents and educators have a great impact on efforts to increase self-confidence.